The Quality Specialities in Turkiye's Honies for Apitherapy - Battaloğlu İnanç Betül (Korean Pharmacopuncture Institute, 2020)
Objectives: In this study, the content of the honey produced by the flora of Turkey', physi-cal, chemical and biological research aimed at active properties.Methods: Searched the database EMBASE/Pubmed and Turkish Medicine Index research article about Turkiye honeys' specialities. Results: Different botanical sources were caused, different kinds of chemical composi-tions of the honeys. The amount of HMF, pH, moisture, and acidity are the chemical qulity criteria of the honey. Carbohydrates are seem the most important components of honey. The glycemic index of the consumed honey is important. Turkiye's honey quality seems ap-ropiate for using apitherapy.Conclusion: Honey is the most important product of beekeeping all over the world in terms of economy and health. Manufacturers of honey should be careful while producing honey. They should be avoided unhealty situations and they should be obey the rules. These rules are the basis for protecting our health by consuming bee products.